Growth Characteristics of Heterosigma akashiwo Virus and Its Possible Use as a Microbiological Agent for Red Tide Control - Nagasaki, Keizo (American Society for Microbiology, 1999)
The growth characteristics of Heterosigma akashiwo virus clone 01 (HaV01) were examined by performing a one-step growth experiment. The virus had a latent period of 30 to 33 h and a burst size of 7.7 × 10(2) lysis-causing units in an infected cell. Transmission electron microscopy showed that the virus particles formed on the peripheries of viroplasms, as observed in a natural H. akashiwo cell. Inoculation of HaV01 into a mixed algal culture containing four phytoplankton species, H. akashiwo H93616, Chattonella antiqua (a member of the family Raphidophyceae), Heterocapsa triquetra (a member of the family Dinophyceae), and Ditylum brightwellii (a member of the family Bacillariophyceae), resulted in selective growth inhibition of H. akashiwo. Inoculation of HaV01 and H. akashiwo H93616 into a natural seawater sample produced similar results. However, a natural H. akashiwo red tide sample did not exhibit any conspicuous sensitivity to HaV01, presumably because of the great diversity of the host species with respect to virus infection. The growth characteristics of the lytic virus infecting the noxious harmful algal bloom-causing alga were considered, and the possibility of using this virus as a microbiological agent against H. akashiwo red tides is discussed.